Dust mass, cloud condensation nuclei, and ice-nucleating particle profiling with polarization lidar: Updated POLIPHON conversion factors from global AERONET analysis - Ansmann, A.; Mamouri, R.-E.; Hofer, J.; Baars, H.; Althausen, D.; Abdullaev, S.F. (Göttingen : Copernicus GmbH, 2019)
The POLIPHON (Polarization Lidar Photometer Networking) method permits the retrieval of particle number, surface area, and volume concentration for dust and non-dust aerosol components. The obtained microphysical properties are used to estimate height profiles of particle mass, cloud condensation nucleus (CCN) and ice-nucleating particle (INP) concentrations. The conversion of aerosol-type-dependent particle extinction coefficients, derived from polarization lidar observations, into the aerosol microphysical properties (number, surface area, volume) forms the central part of the POLIPHON computations. The conversion parameters are determined from Aerosol Robotic Network (AERONET) aerosol climatologies of optical and microphysical properties. In this article, we focus on the dust-related POLIPHON retrieval products and present an extended set of dust conversion factors considering all relevant deserts around the globe. We apply the new conversion factor set to a dust measurement with polarization lidar in Dushanbe, Tajikistan, in central Asia. Strong aerosol layering was observed with mineral dust advected from Kazakhstan (0-2km height), Iran (2-5km), the Arabian peninsula (5-7km), and the Sahara (8-10km). POLIPHON results obtained with different sets of conversion parameters were contrasted in this central Asian case study and permitted an estimation of the conversion uncertainties. Leibniz_Fonds publishedVersion